2017
DOI: 10.1097/fjc.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Free and Nanoencapsulated Copaiba Oil on Monocrotaline-induced Pulmonary Arterial Hypertension

Abstract: Copaiba oil comes from an Amazonian tree and has been used as an alternative medicine in Brazil. However, it has not been investigated yet in the treatment of cardiovascular diseases. This study was designed to test whether copaiba oil or nanocapsules containing this oil could modulate monocrotaline (MCT)-induced pulmonary arterial hypertension (PAH). Male Wistar rats (170 ± 20 g) received oil or nanocapsules containing this oil (400 mg/kg) by gavage daily for 1 week. At the end of this period, a single inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
0
9
0
6
Order By: Relevance
“…In the results reported by other studies with copaiba oil, there are uses of copaiba oil as a vehicle for administration of medicaments, for topical and oral treatment 28,29 , in food technology 30 , dental procedures 30 , and cardiorespiratory processes. 9 Here we can observe a positive result in the use of copaiba oil of 78% according to ►Table 4. This can demonstrate versatility in the use of copaiba oil for different purposes.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the results reported by other studies with copaiba oil, there are uses of copaiba oil as a vehicle for administration of medicaments, for topical and oral treatment 28,29 , in food technology 30 , dental procedures 30 , and cardiorespiratory processes. 9 Here we can observe a positive result in the use of copaiba oil of 78% according to ►Table 4. This can demonstrate versatility in the use of copaiba oil for different purposes.…”
Section: Resultsmentioning
confidence: 67%
“…8 Likewise, the administration of nanoencapsulated copaiba oil significantly reduced the right ventricular hypertrophy of Wistar rats as well as the oxidative stress. 9 In another study, the administration of copaiba oil by gavage reduced the amount of abdominal adhesions and accelerated the formation of collagen fibers without damaging the early stages of healing. 10 Although a large part of the studies showed positive results with the use of copaiba oil, a small part showed that copaiba oil did not show significant results in the applied objectives.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the authors concluded that nanoformulation is more effective on heart tissue than pulmonary circulation. Moreover, the preparation of nanocapsules using pectin aqueous solution with antioxidant effect could have a synergistic effect with copaiba oil and increased pharmacological effect (Campos et al, 2017). Therefore, nanoencapsulation has been known effective in favorable delivery and better efficiency of copaiba oil.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…BCP is one of the most important components of Copaiba oil, popularly used in Brazil for respiratory and cardiovascular illnesses. The nanocapsules of copaiba oil were shown to attenuate monocrotalineinduced pulmonary arterial hypertension in rats by counteracting the oxidative stress and inflammation, and by improving the cardiac function (Campos et al, 2017). One of the major clinical features and reasons for death in COVID-19 patients is respiratory distress syndrome, that also leads to acute cardiac injury .…”
Section: Bcp May Be Prospective In Covid-19 Associated Cardiovascular Conditionsmentioning
confidence: 99%